2019
DOI: 10.1037/ppm0000178
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Facebook on mood in emerging adults.

Abstract: Social media usage is on the rise, with the majority of American adults using Facebook. The present study examined how Facebook activity affects mood in a subset of emerging adults, specifically undergraduates attending a private 4-year university. Participants (N ϭ 312) were randomly assigned to one of the following 20-min activities: browse the Internet, passively browse others' Facebook profiles, actively communicate with others on Facebook via messages/posts, or update their own personal profile on Faceboo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 38 publications
(71 reference statements)
0
32
0
Order By: Relevance
“…Experimental studies in which participants browse content preselected by the researchers (which usually exemplifies especially highly positive self-presentation) have found that Instagram browsing can decrease positive mood, particularly for those who are likely to compare themselves to this content (Weinstein, 2017;de Vries et al, 2018), and can also increase negative mood (Brown and Tiggemann, 2016;Weinstein, 2017). Experiments with "real" SNS content (in which participants log into their personal SNS account and browse others' content) have thus far focused on Facebook, and have found that browsing Facebook can increase negative mood (Fardouly et al, 2015), and decrease positive mood (Yuen et al, 2019). Moreover, browsing one's Facebook news feed can decrease state self-esteem and increase depressive symptoms, although the effects on depressive symptoms may only occur for those with a higher tendency to socially compare (Alfasi, 2019).…”
Section: Browsing Others' Profilesmentioning
confidence: 99%
“…Experimental studies in which participants browse content preselected by the researchers (which usually exemplifies especially highly positive self-presentation) have found that Instagram browsing can decrease positive mood, particularly for those who are likely to compare themselves to this content (Weinstein, 2017;de Vries et al, 2018), and can also increase negative mood (Brown and Tiggemann, 2016;Weinstein, 2017). Experiments with "real" SNS content (in which participants log into their personal SNS account and browse others' content) have thus far focused on Facebook, and have found that browsing Facebook can increase negative mood (Fardouly et al, 2015), and decrease positive mood (Yuen et al, 2019). Moreover, browsing one's Facebook news feed can decrease state self-esteem and increase depressive symptoms, although the effects on depressive symptoms may only occur for those with a higher tendency to socially compare (Alfasi, 2019).…”
Section: Browsing Others' Profilesmentioning
confidence: 99%
“…Ryan et al's review suggests that problematic use of SNSs may allow its users a means to avoid the experience of a negative mood state. However, in contradiction, many other studies have found that using SNSs precipitates a commensurate deterioration in a user's mood; moreover, this decrease is usually attributed to the subjective experience of the banality of SNS use and the feeling that one's time has been wasted on a frivolous activity, Steers et al, 2016 . The evidence appears to suggest that excessive or maladaptive use of SNSs is detrimental to users’ mood states, and this is further underlined by the plethora of research that links problematic SNS use to diminished levels of subjective well‐being.…”
Section: Introductionmentioning
confidence: 98%
“…Given the extraordinary amount of time that people devote to SNSs, a now substantial body of research has emerged that has investigated the reasons motivating the use of SNSs, the personality and psychopathological correlates of excessive SNS use, and the potential consequences SNS use may have for individuals . The totality of this research evidence has converged on the notion that people are motivated to use SNSs to connect with others, to establish new relationships, to maintain existing relationships with friends and family and to browse others’ shared content; thus, the primary benefits to be had from SNS use are greater social capital and the maintenance of relationships …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some of these cases, study design elements were less than ideal from an ecological validity point of view. For example, in some studies, participants were overtly restricted in the ways they could behave, for instance, by prohibiting participants to share posts on Facebook (Tobin et al, 2015; for other examples of restriction, see Deters & Mehl, 2013;Yuen et al, 2019;Verduyn et al, 2015). Other studies clearly manipulated expectations, for instance, by telling participants to expect comments on their posts from coparticipants (thus rendering the fact that participants felt bad when these comments remained absent not particularly surprising, see Tobin et al, 2015).…”
Section: Figurementioning
confidence: 99%